The effectiveness of the Counseling Program to Reduce Burnout among Mother’s Child with Autism - Saeed, Radwan; Muhammed, Jajan (Humanities Journal of University of Zakho, 2020)
The aim of the current research find counseling program Structured in reducing the psychological burnout of mothers of autistic children, and the effect of a counseling program in reducing the psychological burnout of mothers of autistic children, and to achieve this goal requires verification of these hypotheses: There are no statistically significant differences between the experimental group orders and controlled group orders on the scale of Burnout in the pretest . There are no statistically significant differences between the group orders has not been subjected to the Counseling programs of Burnout in Emotional exhaustion in the posttest. There are no statistically significant differences between the group orders has not been subjected to the Counseling programs of Burnout in Depersonalization in the posttest. There are no statistically significant differences between the group orders has not been subjected to the Counseling programs of Burnout in personal accomplishment in the posttest. There are no statistically significant differences between the group orders has not been subjected to the Counseling programs of Burnout generally in the posttest. The research sample consisted of mothers of autistic children in the(Naz) Center for Care and Rehabilitation of Autistic Children, sample was chosen as it reached (14) Mothers a autistic child who was randomly distributed to two groups, one of which is a test (7) mothers and the other is a control ( 7) Mothers, For the purpose of testing the validity of the hypotheses or not, the researcher used the quasi-experimental approach through one group that included (an experimental group and another control with two tests, one pretest and the other posttest). And the equivalence between the members of the two groups in numbers of variables (family size, The economic level of the family, Mother's age, The number of autistic children in the family). The researcher used the Maslach psychological Burnout Inventory scale(MBI) (Maslach,2011) to measure parental burnout, where the number of items of the scale were(22) . The verification of scale validity has been done depending on the method of face validity, the researcher viewed number of in Education and psychology, whereas the reliability was found via the way of split-half was(0.73), and via of re-testing and value was about(0.79)of the scale. The researcher has built a counseling program based on cognitive theory. The number of its sessions reached (16) group counseling sessions. The results of research showed the counseling program have an effect on reducing Burnout among an experimental group of mothers of autistics children. Depending on the results, the researcher has placed a number of recommendations and proposals.